SELECTED INDICATORS OF BONE METABOLISM IN PATIENTS AFTER KIDNEY TRANSPLANT - Al-Jabry, Sadek; Krejčí, Karel; Horčička, Vladko; Štrebl, Pavel; Hrabalová, Monika; Bachleda, Petr; Zadražil, Josef (Biomedical papers, 2003)
Bone metabolism defects and skeleton diseases, so called renal osteopathy (RO), represent very serious clinical problems in the care of patients with kidney dysfunction. Renal osteopathy is a complicated skeletal disorder with a very complicated pathogenesis and we can encounter its individual forms in kidney transplant patients.
Keywords: Renal osteopathy / Kidney transplant / Hyperparathyroidism / Parathormone / Calcitriol / Bone density